Richard Symonds in Rome, 1649-1651 - Brookes, Anne (2000)
This thesis is a study of the notebook (British Library Egerton MS 1635) compiled by Richard Symonds (1617-1670), royalist exile and virtuoso, during his visit to Rome between 1649 to1651. The first volume of the thesis provides an analysis of the chronology of notebooks that Symonds wrote at the time and his methods of study, as well as a detailed reconstruction of his visits to a number of collections. The second volume consists of an annotated transcription of Egerton MS 1635, and an extract from British Library Additional MS 17919 which relates to Symonds's visit to Palazzo Barberini.